Penerapan Komunikasi Interprofessional di Ruang Operasi - Quintas, Ovindiana De Corona Dias; Sriyono, Sriyono; Suarilah, Ira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes published papers on interprofessional communication impelementationin the surgical process. Research Methods: A literature search was conducted in the following database; Scopus, Science Direct, Pubmed, and Proquest, limited toEnglish’s article published from January 2019 to December 2023. Article search results are written based on appropriate protocols and strategies using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) checklist and flow diagrams. Finding/Results:Interprofessional communication has not gone well. There findings are (1) hierarchy between doctors and nurses, (2) lack of knowledge in interprofessional collaboration, and, (3)the need for knowledge and training related to interprofessional communication.Conclusion: The lack of knowledge of team collaboration in communication is influenced by the lack of knowledge of collaboration and interprofessional communication, as well as the perception of hierarchy in providing services. There is a need for further research regarding the factors that influence interprofessional communication knowledge and skills Keywords: Interprofessional Collaboration, Interprofessional Communication, Surgery.